Patient-centered communication, social entrepreneurship motivation, and entrepreneurial intentions in nursing students: A structural equation modelling approach - Larasuci Arini; Afdal Afdal; Ifdil Ifdil; Zadrian Ardi; Mega Iswari Biran Asnah; Nurfarhanah Nurfarhanah (Universitas Airlangga, 2026)
Introduction: The growing demand for homecare nursing in Indonesia offers important career opportunities; however, how clinical competencies are translated into entrepreneurial choices remains unclear. This study examined the relationship between patient-centered communication (PCC) and social entrepreneurship (SE) motivation with nursing students' entrepreneurial intentions (EI) to establish homecare practices. Methods: A cross-sectional survey was conducted with 208 nursing students in West Sumatra, Indonesia. Data collected with validated instruments for EI (α = 0.90), SE drive (α = 0.94), and PCC (α = 0.92) were analyzed using partial least squares structural equation Modelling (PLS-SEM). Results: PLS-SEM showed that PCC did not directly influence EI (β = -0.050, p = 0.669) but significantly predicted SE motivation (β = 0.604, p < 0.001). SE motivation significantly predicted EI (β = 0.627, p < 0.001) and fully mediated the PCC–EI relationship (β indirect = 0.379, p < 0.001). The model explained 35.8% of EI variance. Conclusions: Clinical communication competencies alone do not predict entrepreneurial intentions; rather, they appear to require activation through motivation for social entrepreneurship. Therefore, nursing education should adopt integrated pedagogical frameworks that connect clinical empathy with social-business models to foster homecare as a viable career pathway.